The Effect of Clay Content Towards the Processing of Polypropylene Nano clay Samples in Practical Injection Molding - Isa, Ikmal; Ir. Dr Mohd Hilmi Bin Othman (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This study investigated the effect of nano clay content (3%, 4%, and 5%) on the mechanical properties of polypropylene (PP) nanocomposites produced via injection molding. Samples were processed at temperatures of 160–170°C, an injection pressure of 73 MPa, and injection times of 5–7 seconds. Tensile testing revealed that the 3% nano clay formulation achieved a maximum tensile stress of 28.696 N/mm² and a strain of 16.732%, indicating a balance between strength and elasticity. The 4% nano clay samples exhibited superior mechanical performance with a maximum tensile stress of 33.5 MPa, while the 5% formulation showed reduced strength (29.1 MPa) due to increased viscosity and poor dispersion. The study concludes that 4% nano clay offers the optimal balance of mechanical performance and processability for industrial applications.